Improving students' breaststroke swimming knowledge: Implementation of STAD cooperative learning model based on audiovisual media - Fadillah, Muhammad; Mashud, Mashud (Jurnal Patriot, 2025)
Problems: Swimming is included in physical education subject matter in schools where swimming is not only a physical activity but also requires comprehensive knowledge of basic techniques, safety regulations, and related principles. Purpose: This study aims to determine the effectiveness of the STAD cooperative learning model based on audiovisual media in improving the breaststroke swimming knowledge of class VIII students at MTs Wali Songo. Methods: The study used the Kemmis and Taggart classroom action research model with four implementation stages (planning, action or action, observation, and reflection) with a research sample of 28 class VIII students. The data collection instrument used a test (4 forms of questions), and the analysis technique used quantitative data analyzed descriptively and using a percentage formula. Result: The study's results showed an increase in the percentage of success indicators from the pre-test of 20.43% to 64.29% in cycle one and a rise of 78.57% in cycle two, which exceeded the success indicator of 75%. Conclusion: It can be concluded that in learning breaststroke swimming material for class VIII through the STAD cooperative learning model based on audiovisual media with a span of two cycles, with each cycle having two meetings, the implementation of learning successfully improved students' knowledge.